Higher Education in the Nation's Consciousness - Pifer, Alan.; Carnegie Corp. of New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
In view of the widespread loss of public confidence in higher education, those who understand its importance and continue to put faith in it must be prepared to reargue the case for it. In doing so, however, they must start with a candid admission that during its great period of expansion the academic community did acquire some unattractive faults. Nevertheless, there is much that one can say in support of the academic enterprise. Such a defense can best be started with a reminder of the ways in which higher education's varied functions affect virtually every aspect of the nation's welfare. They may be roughly grouped under three headings: educational, cultural, and socioeconomic. (Author/KE)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annual Reports; Cultural Influences; Educational Benefits; Educational Objectives; Higher Education; Social Influences; Socioeconomic Influences; Reports, Descriptive